A new model for the infrared emission of IRAS F10214+4724 - Efstathiou, A; Christopher, N; Verma, A; Siebenmorgen, R (2011)
We present a new model for the infrared emission of the high redshift hyperluminous infrared galaxy IRAS F10214+4724 which takes into account recent photometric data from Spitzer and Herschel that sample the peak of its spectral energy distribution. We first demonstrate that the combination of the AGN tapered disc and starburst models of Efstathiou and coworkers, while able to give an excellent fit to the average spectrum of type 2 AGN measured by Spitzer, fails to match the spectral energy distribution of IRAS F10214+4724. This is mainly due to the fact that the ν S ν distribution of the galaxy falls very steeply with increasing frequency (a characteristic of heavy absorption by dust) but shows a silicate feature in emission. We propose a model that assumes two components of emission: clouds that are associated with the narrow-line region and a highly obscured starburst. The emission from the clouds must suffer significantly stronger gravitational lensing compared to the emission from the torus to explain the observed spectral energy distribution. © 2012 International Astronomical Union.